Increased risk of incident gout in young men with metabolic syndrome: A nationwide population-based cohort study of 3.5 million men - Yeonghee Eun; Kyungdo Han; Seung Woo Lee; Kyunga Kim; Kyunga Kim; Seonyoung Kang; Seulkee Lee; Hoon-Suk Cha; Eun-Mi Koh; Hyungjin Kim; Hyungjin Kim; Jaejoon Lee (Frontiers in Medicine, 2022)
BackgroundTo date, few studies have focused on risk factors for gout in young people, and large-scale studies on the relationship between metabolic syndrome (MetS) and gout are lacking. We aimed to investigate the association between gout and MetS in a large nationwide population-based cohort of young men who participated in national health examination.Materials and methodsCohort included men aged 20–39 years who participated in a health check-up in 2009–2012. A total of 3,569,104 subjects was included in the study, excluding those who had a previous diagnosis of gout or had renal impairment. The outcome was the occurrence of gout, which was defined using the diagnosis code of gout in the claims database. Cox proportional hazard model was used to evaluate the association between MetS and incident gout.ResultsMean follow-up duration was 7.35 ± 1.24 years and the incidence rate of gout was 3.36 per 1,000 person-years. The risk of gout in subjects with MetS was 2.4-fold higher than subjects without MetS. Among the components of MetS, hypertriglyceridemia and abdominal obesity showed the greatest association with gout. As the number of MetS components increased, the risk of gout increased. The association between gout and MetS was more pronounced in relatively young subjects and in low- or normal-weight subjects.ConclusionMetabolic syndrome is an important risk factor for the gout in young men. In particular, the association between MetS and gout was greater in young and non-obese men. Management of MetS in young men will be important for future gout prevention.